The economy of Greece, 1944-66 : efforts for stability and development - Candilis, Wray O. (New York : Praeger, 1968)
This provides an analysis of the economic activities in Greece from 1944 to 66. It is divided areas like: economic background; efforts for development; pre-requisites for growth.
Includes bibliographical references: p. 223-238.
lje 17/05/2018
Loans
Keywords: Economic conditions; Economic history; Greece